Clinical outcomes in the era of test and treat among children living with HIV: a retrospective before/after study in Zambia - Hamooya, Benson M.; Mutembo, Simon; Siame, Lukundo; Mutalange, Matenge; Cheelo, Chilala; Kamvuma, Kingsley; Muyunda, Brian; Mweebo, Keith; Kancheya, Nzali; Kaayunga, Callistus; Sakala, Morgan; Mvula, Johanzi; et al. (Frontiers in Pediatrics, 2025)
BackgroundInitiating antiretroviral therapy (ART) immediately after diagnosis of HIV infection may reduce morbidity and mortality in children living with HIV (CLHIV), especially when they are retained in HIV care. In Zambia, the retention rate of CLHIV was unknown. The goal of this study was to determine the retention rate and clinical outcomes of implementing a test-and-treat program in children diagnosed with HIV infection.MethodsWe conducted a retrospective before/after study in 42 health facilities in 12 districts of the southern region of Zambia. We reviewed case files of CLHIV initiated on ART before the test-and-treat (BTT) policy (1 January 2014 to 31 July 2016; n = 405) and after implementation of the test-and-treat (ATT) policy (1 August 2016 to 1 October 2020; n = 579). We collected demographic, laboratory, and clinical data using a structured data collection form in REDCap. The primary outcome was retention defined as regular attending of appointments or engagement with the ART clinic at 3, 6, 12, 24, and ≥24 months after ART initiation. Descriptive statistics and logistic regression were the statistical methods employed.ResultsThe median age of 984 CLHIV was 60 months (interquartile range [IQR] 22–100) and 52.3% (n = 515) were girls. The overall retention rate (alive and on treatment) was 82.0% (n = 807; 95% confidence interval [CI] 79.5–84.4) after 24 months. A higher proportion of children ATT were retained in care compared to those BTT (91.0% vs. 69.1%; p < 0.001). More of the children BTT were transferred out (19.0% vs. 4.8%; p < 0.001) and lost to follow-up (11.1% vs. 3.8%; p < 0.001) compared to those in the ATT cohort. In addition, there was a significant improvement in the proportion of children in World Health Organization (WHO) clinical stage 1, increasing from 83% to 98% among those retained in care at the end of follow-up. In the multivariable analysis, factors associated with higher odds of retention included being in the ATT cohort (adjusted odds ratio [aOR] 4.98; 95% CI 4.06–6.11) and use of a dolutegravir (DTG)-based regimen (aOR 2.66; 95% CI 1.05–6.72). In contrast, being female (aOR 0.80; 95% CI 0.67–0.95), a longer duration from HIV diagnosis to ART initiation (aOR 0.99; 95% CI 0.99–0.99), and being in WHO clinical stage 3 (aOR 0.68; 95% CI 0.52–0.90) or stage 4 (aOR 0.30; 95% CI 0.19–0.48) were negatively associated with retention in care.ConclusionRetention was significantly higher among children enrolled in the test-and-treat (ATT) cohort and those on a DTG-based regimen. In contrast, female sex, longer time to ART initiation after HIV diagnosis, and advanced WHO clinical stages were associated with lower odds of retention. However, retention improved as well as clinical outcomes in ATT compared to BTT after 24 months. This study underscores the importance of initiating ART immediately after diagnosis of HIV to enhance retention in HIV care and treatment. Therefore, improving ART retention by enhancing interventions in resource-limited settings can be highly beneficial.